Biodegradable Film

The biodegradable film, made from a hydroxyalkanoate-lactide copolymer and PBAT, addresses the issues of low mechanical properties and poor compatibility in existing films, resulting in improved tensile strength and biomaterial content while maintaining eco-degradability.

JP2025509023APending Publication Date: 2025-04-11LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024537559
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-03-07
Filing Date
2023-03-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing biodegradable mulching films face challenges with low mechanical properties such as Young's modulus and poor compatibility with other biodegradable materials, leading to inadequate tensile strength and low biomaterial content.

Method used

A biodegradable film composed of a hydroxyalkanoate-lactide copolymer and polybutylene adipate terephthalate (PBAT), which exhibits excellent compatibility and tensile properties like yield tensile strength and Young's modulus, while maintaining a high biomaterial content.

Benefits of technology

The biodegradable film achieves enhanced tensile properties and increased biomaterial content, ensuring eco-degradability and improved mechanical performance compared to traditional films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509023000001_ABST
    Figure 2025509023000001_ABST
Patent Text Reader

Abstract

In the present invention, a biodegradable film is provided that includes a hydroxyalkanoate-lactide copolymer and polybutylene adipate terephthalate (PBAT).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0030178 dated March 10, 2022, Korean Patent Application No. 10-2022-0030177 dated March 10, 2022, and Korean Patent Application No. 10-2023-0029596 dated March 7, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a biodegradable film. [Background technology]

[0003] Recently, interest in environmental protection and ecology has increased sharply, and the need for methods to cultivate eco-friendly agricultural products is growing. Mulching farming is one such eco-farming method, which is a method of covering the soil surface with mulching film when cultivating crops to prevent the growth of weeds, prevent damage from pests, retain moisture in the soil or regulate the soil temperature, prevent soil erosion by rainwater during rainy days, and reduce the use of pesticides.

[0004] Mulching films used in this type of farming greatly contribute to the productivity of agricultural produce, but they are difficult to remove and recycle after use. Usually, synthetic resins such as polypropylene and polyethylene are used and biodegradable components are added as additives to impart biodegradability, but the reality is that synthetic resins themselves are not biodegradable. In addition, synthetic resins that remain without being biodegraded have the problem of polluting the soil.

[0005] For this reason, there have been attempts to manufacture mulching films using polybutylene adipate terephthalate (PBAT), a biodegradable plastic, but while PBAT has a high elongation rate, it has problems with its mechanical properties, such as Young's modulus, being lower than existing films such as polyethylene.In addition, since PBAT is a 100% petroleum-based material, it has a low content of bio-based raw materials.

[0006] Therefore, attempts have been made to compound polybutylene adipate terephthalate (PBAT) with various biodegradable materials to improve its physical properties and increase the content of bio-based raw materials, but this has problems such as poor compatibility between polybutylene adipate terephthalate and other biodegradable materials, resulting in poor tensile properties. Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention provides a biodegradable film having excellent tensile properties such as yield tensile strength and Young's modulus, and an increased content of biomaterials. [Means for solving the problem]

[0008] According to one embodiment of the present invention, there is provided a biodegradable film comprising a hydroxyalkanoate-lactide copolymer and polybutylene adipate terephthalate (PBAT).

[0009] Hereinafter, the biodegradable film according to the specific embodiment of the present invention will be described in more detail.

[0010] Throughout this specification, unless otherwise specified, the words "comprise" or "contain" refer to the inclusion of a certain component (or ingredient) without specific limitation, and should not be interpreted as excluding the addition of other components (or ingredients).

[0011] Throughout this specification, the term "polylactic acid prepolymer" refers to a polylactic acid having a weight average molecular weight of 1,000 to 50,000 g / mol obtained by oligomerizing lactic acid.

[0012] Throughout this specification, the term "poly(3-hydroxypropionate) prepolymer" refers to poly(3-hydroxypropionate) having a weight average molecular weight of 1,000 to 50,000 g / mol obtained by oligomerizing 3-hydroxypropionate.

[0013] In addition, unless otherwise specified in this specification, the weight average molecular weight of polylactate prepolymer, poly(3-hydroxypropionate) prepolymer, and copolymer can be measured using gel permeation chromatography (GPC). Specifically, the prepolymer or copolymer is dissolved in chloroform to a concentration of 2 mg / ml, and then 20 μl is injected into GPC and GPC analysis is performed at 40 ° C. At this time, chloroform is used as the mobile phase of GPC, and the flow rate is 1.0 mL / min, two Agilent Mixed-B columns are connected in series, and an RI Detector is used as the detector. The Mw value is derived using a calibration curve formed using a polystyrene standard specimen. Nine types of polystyrene standard specimens with weight average molecular weights of 2,000 g / mol, 10,000 g / mol, 30,000 g / mol, 70,000 g / mol, 200,000 g / mol, 700,000 g / mol, 2,000,000 g / mol, 4,000,000 g / mol, and 10,000,000 g / mol were used.

[0014] In addition, the term "substituted or unsubstituted" in the present specification means a group selected from the group consisting of deuterium, halogen, nitrile, nitro, hydroxy, carbonyl, ester, imide, amino, phosphine oxide, alkoxy, aryloxy, alkylthio, arylthio, alkylsulfoxy, arylsulfoxy, silyl, boron, alkyl, cycloalkyl, alkenyl, aryl, aralkyl, aralkenyl, alkylaryl, alkylamine, aralkylamine, heteroarylamine, arylamine, arylphosphine, or heterocyclic groups containing one or more of N, O, and S atoms, or a group selected from the group consisting of the above-listed substituents and two or more of the above-listed substituents. For example, the "substituent having two or more substituents connected" may be a biphenyl group. In other words, the biphenyl group may be an aryl group, and may be interpreted as a substituent having two phenyl groups connected.

[0015] Conventionally, biodegradable films have been produced by using only polybutylene adipate terephthalate or by compounding polybutylene adipate terephthalate with other biodegradable materials. However, when only polybutylene adipate terephthalate is used, there are problems such as low mechanical properties such as Young's modulus and low content of biomaterials, and when polybutylene adipate terephthalate is compounded with other biodegradable materials, there are problems such as low compatibility between the materials and low tensile properties.

[0016] In this regard, the present inventors discovered that a biodegradable film manufactured by compounding polybutylene adipate terephthalate (PBAT) with a hydroxyalkanoate-lactide copolymer has excellent compatibility between the materials and excellent tensile properties such as yield tensile strength and Young's modulus, and thus completed the present invention.

[0017] In addition, since the hydroxyalkanoate-lactide copolymer exhibits eco-friendly and biodegradable properties while containing a large amount of biomaterials, a biodegradable film containing the copolymer can also contain a large amount of biomaterials while maintaining eco-friendly and biodegradable properties.

[0018] According to one embodiment of the invention, a biodegradable film is provided that includes a hydroxyalkanoate-lactide copolymer and polybutylene adipate terephthalate (PBAT).

[0019] The hydroxyalkanoate-lactide copolymer included in the biodegradable film according to one embodiment may be a block copolymer including one or more polyhydroxyalkanoate (PHA) blocks and one or more polylactic acid blocks. By including the above-mentioned blocks, the hydroxyalkanoate-lactide copolymer can exhibit the eco-friendliness and biodegradability of polyhydroxyalkanoate and polylactic acid.

[0020] The hydroxyalkanoate may be 3-hydroxybutyrate, 4-hydroxybutyrate, 2-hydroxypropionate, 3-hydroxypropionate, (D)-3-hydroxycarboxylate with a medium chain length of 6 to 14 carbon atoms, 3-hydroxyvalerate, 4-hydroxyvalerate, or 5-hydroxyvalerate. Thus, the hydroxyalkanoate-lactide copolymer may be 3-hydroxybutyrate-lactide copolymer, 4-hydroxybutyrate-lactide copolymer, 2-hydroxypropionate-lactide copolymer, 3-hydroxypropionate-lactide copolymer, 4-hydroxyvalerate-lactide copolymer, or 5-hydroxyvalerate-lactide copolymer, and for example, the hydroxyalkanoate-lactide copolymer may be 3-hydroxypropionate-lactide copolymer in order to improve flexibility, mechanical properties, etc.

[0021] The 3-hydroxypropionate-lactide copolymer may be a block copolymer in which a polylactic acid prepolymer and a poly(3-hydroxypropionate) prepolymer are polymerized.

[0022] The 3-hydroxypropionate-lactide copolymer exhibits excellent tensile strength and elastic modulus characteristics of the polylactic acid prepolymer, while the poly(3-hydroxypropionate) prepolymer lowers the glass transition temperature (Tg), increases flexibility, and improves mechanical properties such as impact strength, thereby preventing the poor elongation and brittleness of polylactic acid.

[0023] The polylactic acid prepolymer may be prepared by fermenting or polycondensing lactic acid.

[0024] The polylactic acid prepolymer may have a weight average molecular weight of 1,000 g / mol or more, or 5,000 g / mol or more, or 6,000 g / mol or more, or 8,000 g / mol or more, and 50,000 g / mol or less, or 30,000 g / mol or less. When it is intended to increase the crystallinity of the block containing the repeating unit derived from the polylactic acid prepolymer in the final block copolymer, it is preferable that the polylactic acid prepolymer has a high weight average molecular weight of more than 20,000 g / mol, or 22,000 g / mol or more, or 23,000 g / mol or more, or 25,000 g / mol or more, and 50,000 g / mol or less, or 30,000 g / mol or less, or 28,000 g / mol or less, or 26,000 g / mol or less.

[0025] If the weight average molecular weight of the polylactic acid prepolymer is less than 20,000 g / mol, the crystallinity of the polymer is small, making it difficult to maintain the crystallinity of the polymer in the final block copolymer. If the weight average molecular weight of the polylactic acid prepolymer is more than 50,000 g / mol, the rate of side reactions occurring within the prepolymer chain during polymerization becomes faster than the rate of reaction between the polylactic acid prepolymers.

[0026] On the other hand, "lactic acid" as used in the present invention refers to L-lactic acid, D-lactic acid, or a mixture thereof.

[0027] The poly(3-hydroxypropionate) prepolymer may be produced by fermentation or condensation polymerization of 3-hydroxypropionate.

[0028] The weight average molecular weight of the poly(3-hydroxypropionate) prepolymer may be 1,000 g / mol or more, or 5,000 g / mol or more, or 8,000 g / mol or more, or 8,500 g / mol or more, and 50,000 g / mol or less, or 30,000 g / mol or less. When it is desired to increase the crystallinity of the repeating units derived from the poly(3-hydroxypropionate) prepolymer in the final block copolymer produced, it is preferred that the poly(3-hydroxypropionate) prepolymer has a high weight average molecular weight of more than 20,000 g / mol, or 22,000 g / mol or more, or 25,000 g / mol or more, and 50,000 g / mol or less, or 30,000 g / mol or less, or 28,000 g / mol or less.

[0029] As explained in the polylactide prepolymer, if the weight average molecular weight of the poly(3-hydroxypropionate) prepolymer is less than 20,000 g / mol, the polymer crystals are small, making it difficult to maintain the polymer crystallinity in the final block copolymer. If the weight average molecular weight of the poly(3-hydroxypropionate) prepolymer exceeds 50,000 g / mol, the rate of side reactions occurring within the prepolymer chain during polymerization becomes faster than the rate of reaction between the poly(3-hydroxypropionate) prepolymers.

[0030] That is, at least one of the polylactic acid prepolymer and the poly(3-hydroxypropionate) prepolymer may have a weight average molecular weight of more than 20,000 g / mol and not more than 50,000 g / mol.

[0031] Meanwhile, the lactic acid and 3-hydroxypropionate may be plastic and biodegradable compounds produced from renewable sources by microbial fermentation, and the block copolymer containing polylactic acid prepolymer and poly(3-hydroxypropionate) prepolymer formed by polymerizing them can also exhibit eco-friendliness and biodegradability. Thus, the biodegradable film containing the block copolymer can contain a large amount of biomaterials while exhibiting eco-friendliness and biodegradability.

[0032] The 3-hydroxypropionate-lactide copolymer is a block copolymer obtained by polymerizing a polylactic acid prepolymer and a poly(3-hydroxypropionate) prepolymer, and the weight ratio of the polylactic acid prepolymer to the poly(3-hydroxypropionate) prepolymer in the block copolymer may be 95:5 to 50:50, 90:10 to 55:45, 90:10 to 60:40, 90:10 to 70:30, or 90:10 to 80:20. If the poly(3-hydroxypropionate) prepolymer is contained in an excessively small amount relative to the polylactic acid prepolymer, the brittleness may increase, and if the poly(3-hydroxypropionate) prepolymer is contained in an excessively large amount relative to the polylactic acid prepolymer, the molecular weight may decrease, leading to reduced processability and heat resistance.

[0033] As described above, the 3-hydroxypropionate-lactide copolymer contains one or more poly(3-hydroxypropionate) blocks and one or more polylactic acid blocks, and can exhibit high crystallinity.

[0034] For example, the 3-hydroxypropionate-lactide copolymer has a crystallinity (Xc_ ) of the polylactic acid block in the copolymer, which is calculated by the following Equations 1 and 2 using the crystallization temperature and melting temperature measured by differential scanning calorimetry. PLA ) is more than 0 and less than 50, or the crystallinity (Xc_ P(3HP) ) may be 0 to 50, or more than 0 and 50 or less.

[0035] In addition, the total crystallinity of the polylactic acid block and the poly(3-hydroxypropionate) block in the copolymer may be 20 to 100, more specifically, 20 or more, or 30 or more, or 32 or more, and 100 or less, or 70 or less, or 50 or less, or 48 or less.

[0036] By satisfying the above-mentioned crystallinity, the copolymer has a well-balanced improvement in flexibility and mechanical properties, and can simultaneously exhibit the excellent strength characteristics of polylactic acid and the excellent elongation characteristics of poly(3-hydroxypropionate).

[0037] On the other hand, if the total crystallinity is too high, the biodegradability and processability may decrease, and if the total crystallinity is too low, the strength may decrease. [Formula 1] The crystallinity of the polylactic acid block (Xc PLA )=[(PLA Tm area)-(PLA Tcc area)] / 93.7

[0038] In Equation 1, the PLA Tm area may be an integral value of a peak at the melting temperature (Tm) of the polylactic acid (PLA) block in the block copolymer measured by differential scanning calorimetry, and the PLA Tcc area may be an integral value of a peak at the crystallization temperature (Tcc) of the polylactic acid block in the block copolymer measured by differential scanning calorimetry. [Formula 2]

[0039] The crystallinity of the poly(3-hydroxypropionate) block (Xc P(3HP) )=[(P(3HP) Tm area)-(P(3HP) Tcc area)] / 64

[0040] In Equation 2, the P(3HP) Tm area may be an integral value of a peak at the melting temperature (Tm) of the poly(3-hydroxypropionate) (P(3HP)) block in the block copolymer measured through differential scanning calorimetry, and the P(3HP) Tcc area may be an integral value of a peak at the crystallization temperature (Tcc) of the poly(3-hydroxypropionate) block in the block copolymer measured through differential scanning calorimetry.

[0041] The integral values ​​for the peaks at Tm and Tcc refer to values ​​obtained by integrating the areas under the peaks indicating Tm and Tcc, respectively.

[0042] Here, the differential scanning calorimetry analysis for measuring Tm and Tcc of each block may be performed using a PerkinElmer DSC 800. Also, the sample to be analyzed may be heated from 25°C to 250°C at a rate of 10°C per minute in a nitrogen atmosphere, cooled from 250°C to -50°C at a rate of -10°C per minute, and then heated from -50°C to 250°C at a rate of 10°C per minute to obtain an endothermic curve, thereby confirming Tm and Tcc.

[0043] The hydroxyalkanoate-lactide copolymer has a weight average molecular weight (Mw) of 50,000 to 300,000 g / mol, more specifically, 50,000 g / mol or more, 70,000 g / mol or more, or 100,000 g / mol or more, and 300,000 g / mol or less, or 200,000 g / mol or less, or 150,000 g / mol or less, as measured by gel permeation chromatography (GPC). If the weight average molecular weight of the hydroxyalkanoate-lactide copolymer is too small, the overall mechanical properties may be significantly reduced, and if the weight average molecular weight is too large, the process may be difficult, and the processability and elongation may be reduced.

[0044] The biodegradable film according to one embodiment includes the hydroxyalkanoate-lactide copolymer, and may be included in an amount of, for example, 3 to 40% by weight, based on a total weight of 100% of the biodegradable film, and more specifically, may be included in an amount of 3% by weight or more, 5% by weight or more, 7% by weight or more, or 40% by weight or less, 35% by weight or less, 30% by weight or less.

[0045] If the hydroxyalkanoate-lactide copolymer is contained in the biodegradable film in an excessively small amount, the tensile properties such as Young's modulus and yield tensile strength may be reduced, and if the hydroxyalkanoate-lactide copolymer is contained in the biodegradable film in an excessively large amount, the elongation may be reduced.

[0046] The biodegradable film according to one embodiment includes polybutylene adipate terephthalate (PBAT).

[0047] The polybutylene adipate terephthalate (PBAT) is a biodegradable resin and may be contained in an amount of 30 to 98% by weight, more specifically, 30% by weight or more, 40% by weight or more, 50% by weight or more, or 98% by weight or less, 95% by weight or less, or 92% by weight or less, based on the total weight of the biodegradable film.

[0048] When the polybutylene adipate terephthalate (PBAT) is contained in a biodegradable film in an excessively small amount, the elongation may be decreased, and when the polybutylene adipate terephthalate (PBAT) is contained in a biodegradable film in an excessively large amount, the tensile properties such as Young's modulus and yield tensile strength may be decreased.

[0049] The weight ratio of the hydroxyalkanoate-lactide copolymer and polybutylene adipate terephthalate (PBAT) contained in the biodegradable film according to the embodiment may be 5:95 to 50:50, 5:95 to 40:60, or 10:90 to 30:70. If the amount of polybutylene adipate terephthalate (PBAT) is too small compared to the hydroxyalkanoate-lactide copolymer, the elongation may be low, and if the amount of polybutylene adipate terephthalate (PBAT) is too large compared to the hydroxyalkanoate-lactide copolymer, the tensile properties such as Young's modulus and yield tensile strength may be reduced.

[0050] The biodegradable film according to an embodiment may further include thermoplastic starch. The present inventors have discovered that a biodegradable film produced by compounding polybutylene adipate terephthalate (PBAT) with a hydroxyalkanoate-lactide copolymer and thermoplastic starch has excellent compatibility between the materials and also has excellent tensile properties such as yield tensile strength and Young's modulus.

[0051] Additionally, the biodegradable film may further comprise thermoplastic starch to enhance the processability and increase the biodegradation rate of the polybutylene adipate terephthalate.

[0052] The thermoplastic starch may be starch that is a natural polymer and is provided with thermoplasticity by adding a plasticizer to starch, which is a natural polymer and is not carbonized even at a certain temperature or higher, unlike existing general-purpose resins such as polyethylene, polystyrene, and polypropylene, and is capable of freely changing its shape.

[0053] The thermoplastic starch may include one or more selected from the group consisting of rice starch, wheat starch, corn starch, sweet potato starch, potato starch, tapioca starch, cassava starch, and modified starches thereof.

[0054] In addition, the plasticizer contained in starch, which is a natural polymer, may be one or more selected from the group consisting of isosorbide, glycerol, sorbitol, fructose, formamide, xylitol, corn oil, and salad oil.

[0055] The plasticizer may be present in an amount of from 5% to 50% by weight, from 10% to 45% by weight, or from 15% to 35% by weight, based on a total of 100% by weight of the thermoplastic starch.

[0056] The thermoplastic starch may be contained in an amount of 10 to 70% by weight, more specifically, 10% by weight or more, 15% by weight or more, 20% by weight or more, or 70% by weight or less, 60% by weight or less, 50% by weight or less, based on the total weight of the biodegradable film.

[0057] If the thermoplastic starch is contained in the biodegradable film in an amount that is too small, the biodegradation rate may be slow and tensile properties such as Young's modulus and yield tensile strength may be reduced, and if the thermoplastic starch is contained in the biodegradable film in an amount that is too large, the elongation may be low.

[0058] As described above, the biodegradable film may contain 10 to 100 parts by weight, 20 to 90 parts by weight, 30 to 80 parts by weight, or 30 to 70 parts by weight of the thermoplastic starch, based on a total of 100 parts by weight of the hydroxyalkanoate-lactide copolymer and the polybutylene adipate terephthalate (PBAT).

[0059] The biodegradable film according to one embodiment may further include a compatibilizer to improve the binding strength of the hydroxyalkanoate-lactide copolymer and polybutylene adipate terephthalate (PBAT) and improve mechanical properties. The compatibilizer can improve the binding strength of the hydroxyalkanoate-lactide copolymer, polybutylene adipate terephthalate (PBAT) and thermoplastic starch and improve mechanical properties. The compatibilizer can act as a chain extender to increase the molecular weight, increase the melt viscosity, and improve formability such as stretchability.

[0060] The compatibilizer may be, but is not limited to, a compound containing at least one functional group selected from a glycidyl group, an acid anhydride group, a carbodiimide group, an isocyanate group, an oxazoline group, and an amino group.

[0061] Examples of the compound containing a glycidyl group include a glycidyl ether compound, a glycidyl ester compound, a glycidyl amine compound, a glycidyl imide compound, a glycidyl (meth)acrylate compound, and an alicyclic epoxy compound. Examples of commercially available compounds include the "BIOMAX" (registered trademark) Strong series of DuPont, which is a copolymer of ethylene, an acrylic acid ester, and a glycidyl (meth)acrylate, the "LOTADER" (registered trademark) series of Arkema, the "JONCRYL" (registered trademark) series of BASF, which is an acrylic / styrene copolymer containing a glycidyl group, the "Reseda" (registered trademark) series of Toa Gosei Co., Ltd., which is an acrylic resin containing a glycidyl group, and the "Arfon" (registered trademark) series of the same company. Examples of the compound containing an acid anhydride group include compounds containing succinic anhydride, maleic anhydride, phthalic anhydride, etc. Examples of commercially available compounds include the "BONDINE" (registered trademark) series of Arkema Co., Ltd., which is a copolymer of ethylene, acrylic acid ester, and maleic anhydride, the "OREVAC" (registered trademark) series of Arkema Co., Ltd., which is a maleic anhydride graft polymer, the "Bynel" series of DuPont Co., Ltd., the "UMEX" (registered trademark) series of Sanyo Chemical Industries, Ltd., and the "KRATON" (registered trademark) series of Kraton Co., Ltd., which is a copolymer of styrene-ethylene-butylene-styrene copolymer (SEBS) and maleic anhydride. The compound containing a carbodiimide group is a compound having at least one carbodiimide group represented by (-N=C=N-) in the molecule, and examples of commercially available compounds include the "CARBODILITE" (registered trademark) series of Nisshinbo Co., Ltd. and the "STABAXOL" (registered trademark) series of Rhein Chemie Co., Ltd. Examples of compounds containing an isocyanate group include hexamethylene diisocyanate.

[0062] For example, the compatibilizer may include a repeating unit represented by the following Formula 1: [Chemical formula 1] [ka] In the above Chemical Formula 1, R1 to R6 may each independently be hydrogen, deuterium, hydroxy, nitro, amino, a substituted or unsubstituted alkyl having 2 to 60 carbon atoms, a substituted or unsubstituted alkoxy having 2 to 60 carbon atoms, a substituted or unsubstituted alkenyl having 2 to 60 carbon atoms, a substituted or unsubstituted cycloalkyl having 4 to 60 carbon atoms, a substituted or unsubstituted aryl having 6 to 60 carbon atoms, or a substituted or unsubstituted heteroaryl having 2 to 60 carbon atoms containing one or more of O, N, Si, and S.

[0063] For example, R1 through R3 may each independently be hydrogen or deuterium.

[0064] Additionally, R4 and R6 may each independently be hydrogen, deuterium, methyl, ethyl, or propyl.

[0065] Also, R5 may be an alkyl group having 2 to 60 carbon atoms. x, y, and z may each independently be an integer from 1 to 20.

[0066] The compatibilizer may be included in an amount of 0.1 to 10 parts by weight, more specifically, 0.1 part by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, or 10 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less, based on 100 parts by weight of the biodegradable film.

[0067] If the compatibilizer is contained in the biodegradable film in an amount that is too small, the mechanical properties may not be improved, and if the compatibilizer is contained in the biodegradable film in an amount that is too large, the melting point may become too high, resulting in reduced moldability.

[0068] The biodegradable film according to an embodiment may have a yield tensile strength, as measured by ASTM D882-07, of 7 MPa or more, 8 MPa or more, or 7 MPa to 30 MPa.

[0069] The biodegradable film may have a Young's modulus, measured according to ASTM D882-07, of 80 MPa or more, 85 MPa or more, 90 MPa or more, or 100 MPa to 800 MPa. The thickness of the biodegradable film according to one embodiment may be 10 to 300 μm, more specifically, 10 μm or more, 20 μm or more, 30 μm or more, or 300 μm or less, 200 μm or less, 150 μm or less. When the thickness of the film is within the above range, the film has strong elasticity, excellent handleability, and good winding and unwinding properties of the roll.

[0070] If the film thickness is too thin, the tensile strength, tear strength, and elongation may be poor, and the film may develop holes or break during use. If the film thickness is too thick, the unit price may be less competitive.

[0071] The biodegradable film can be used as an agricultural mulching film, disposable gloves, individual medical packaging paper, food packaging paper, garbage bags, bags for various industrial products, and the like.

[0072] The method for producing the biodegradable film is not particularly limited, but a melt-kneading method in which hydroxyalkanoate-lactide copolymer, polybutylene adipate terephthalate (PBAT) and / or thermoplastic starch are melt-kneaded may be used, or a solution in which each component is dissolved in a solvent may be uniformly mixed, and then the solvent may be removed to produce a composition.

[0073] In the case of the melt-kneading method, the method is not particularly limited, but a common mixer such as a kneader, a roll mill, a Benber mixer, a single-screw or twin-screw extruder, etc. The temperature of the extruder during melt-kneading may be 150°C to 240°C, 160°C to 220°C, or 170°C to 200°C.

[0074] The biodegradable film can be obtained by using a composition produced by a melt kneading method, etc., and by a known film production method such as an inflation method, a tubular method, a T-die casting method, etc. For example, the composition can be pelletized, and the pellets can be dried at 60 to 100° C. for 6 hours or more to control the moisture content to 1,200 ppm or less, 500 ppm or less, or 200 ppm or less.

[0075] The pelletized composite can then be applied to a release film, placed in a thermocompression machine, and pressed to produce a film, at a temperature of 130° C. to 250° C., 150° C. to 220° C., or 160° C. to 200° C. and a pressure of 5 MPa to 20 MPa, 8 MPa to 17 MPa, or 10 MPa to 15 MPa. Effect of the Invention

[0076] According to the present invention, it is possible to provide a biodegradable film containing biomaterials, which has excellent tensile properties such as yield tensile strength and Young's modulus while maintaining eco-friendliness and biodegradability. [Brief description of the drawings]

[0077] [Figure 1] 1 shows stress-strain curves for films prepared in Examples 1 to 4 and Comparative Example 1. [Diagram 2] 1 shows stress-strain curves for films prepared in Examples 5 to 9 and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0078] The present invention will be described in more detail with reference to the following examples. However, the following examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples.

[0079] Preparation Example 1: Preparation of 3-hydroxypropionate-lactide block copolymer (1) Production of polylactic acid prepolymer 25g of 85% L-lactic acid aqueous solution was added to a 100ml Schlenk flask in an oil bath, and the water content in the L-lactic acid was removed by reducing the pressure at 70℃ and 50mbar for 2 hours. Then, 0.4 parts by weight of p-toluenesulfonic acid (p-TSA) and 0.1 parts by weight of SnCl2 catalyst were added based on 100 parts by weight of lactate, and melt polycondensation reaction was carried out at a temperature of 150℃ for 12 hours. After the reaction was completed, the reactant was dissolved in chloroform and extracted with methanol to obtain a polylactic acid prepolymer (weight average molecular weight: 8,000g / mol).

[0080] (2) Preparation of poly(3-hydroxypropionate) prepolymer 25 ml of 60% 3-hydroxypropionate aqueous solution was added to a 100 ml Schlenk flask in an oil bath, and moisture in the 3-hydroxypropionate was removed at 50° C. and 50 mbar for 3 hours, and then oligomerization was performed for 2 hours at 70° C. and 20 mbar. Then, 0.4 parts by weight of p-toluenesulfonic acid (p-TSA) catalyst was added to the reaction flask based on 100 parts by weight of 3-hydroxypropionate, and melt polycondensation reaction was performed for 24 hours at a temperature of 110° C. After the reaction was completed, the reactant was dissolved in chloroform and extracted with methanol to obtain poly(3-hydroxypropionate) prepolymer (weight average molecular weight: 26,000 g / mol).

[0081] (3) Production of block copolymers The polylactate prepolymer and the poly(3-hydroxypropionate) prepolymer were mixed in a weight ratio of 9:1 and added to a 100 ml Schlenk flask in an oil bath to a total content of 30 g, and then 90 mg of p-toluenesulfonic acid (p-TSA) was added and annealed for 3 hours at 60° C. Then, the mixture was mixed for 24 hours using an evaporator under conditions of 150° C. and 0.5 mbar to carry out a solid-state polymerization reaction, thereby producing a 3-hydroxypropionate-lactide block copolymer (weight average molecular weight: 130,000 g / mol). On the other hand, the weight average molecular weights of the polylactic acid prepolymer, poly(3-hydroxypropionate) prepolymer and block copolymer were measured by gel permeation chromatography (GPC).

[0082] Production Example 2: Production of thermoplastic starch 225 g of corn starch and 75 g of glycerol were mixed in a mixer and then compounded in an extruder. The temperature range of the extruder was 80 to 150°C, the screw speed was set at 150 rpm, and the extruded strands were cut with a pelletizer to produce thermoplastic starch pellets.

[0083] <Examples and Comparative Examples> Example 1: Preparation of a biodegradable film 90 g of polybutylene adipate terephthalate (PBAT, Solpol 1000N, SOLTECH) and 10 g of the 3-hydroxypropionate-lactide block copolymer prepared in Preparation Example 1 were hand-mixed based on dry weight, and then compounded by feeding into an extruder. The temperature range of the extruder was 170 to 190°C, and the screw speed was set to 150 rpm, and the extruded strand was cut with a pelletizer to prepare composite pellets. The prepared composite pellets were coated on a release film and then placed in a thermocompression machine, where a pressure of 12 MPa was applied at 190°C to prepare a film having a thickness of 100 μm.

[0084] Examples 2 to 5 and Comparative Example 1: Preparation of biodegradable films A film was produced in the same manner as in Example 1, except that the contents of polybutylene adipate terephthalate, 3-hydroxypropionate-lactide block copolymer, and compatibilizer (Joncryl (registered trademark) ADR 4468, BASF) were used as shown in Table 1 below. Meanwhile, in Table 1, "-" means none. [Table 1]

[0085] Example 5: Preparation of biodegradable film Based on the dry weight, 42 g of polybutylene adipate terephthalate (PBAT, Solpol 1000N, SOLTECH), 18 g of the 3-hydroxypropionate-lactide block copolymer prepared in Preparation Example 1, 40 g of the thermoplastic starch prepared in Preparation Example 2, and 0.5 g of a compatibilizer (Joncryl® ADR 4468, BASF) were hand-mixed and then compounded in an extruder. The temperature range of the extruder was 170 to 190°C, the screw speed was set to 150 rpm, and the extruded strand was cut with a pelletizer to prepare composite pellets. The prepared composite pellets were coated on a release film and then placed in a thermocompression machine, where a pressure of 12 MPa was applied at 160°C to prepare a film having a thickness of 100 μm.

[0086] Examples 6 to 9 and Comparative Example 2: Preparation of biodegradable films A film was produced in the same manner as in Example 5, except that the contents of polybutylene adipate terephthalate, 3-hydroxypropionate-lactide block copolymer, thermoplastic starch and compatibilizer were used as shown in Table 2 below. Meanwhile, in Table 2, "-" means none.

[0087] Comparative Example 3: Production of biodegradable film 90g of polybutylene adipate terephthalate (PBAT, Solpol 1000N, SOLTECH) and 10g of polylactic acid (PLA, product name: PLA 2003D, NATUREWORKS) were mixed by hand based on dry weight, and then compounded by feeding into an extruder. The temperature range of the extruder was 170-190°C, the screw speed was set to 150 rpm, and the extruded strand was cut with a pelletizer to produce composite pellets. The produced composite pellets were coated on a release film and then placed in a thermocompression machine, where a pressure of 12 MPa was applied at 190°C to produce a film with a thickness of 100 μm. [Table 2]

[0088] evaluation 1. Evaluation of tensile properties The tensile properties of the films of the examples and comparative examples were evaluated according to ASTM D882-07, including yield tensile strength, Young's modulus, ultimate tensile strength, and elongation at break, and the results are shown in Tables 3 and 4 below.

[0089] Yield tensile strength is the maximum stress at which permanent inelastic deformation begins. The yield point is the point (load) at which a material yields, i.e., an increase in deformation occurs without an increase in stress. Young's modulus is the ratio of stress to deformation in the elastic region of the stress-strain curve (before the yield point). Ultimate tensile strength is the maximum stress a material can withstand before breaking. Elongation at break is the percentage deformation at break, or the percentage change in length at break.

[0090] FIG. 1 shows stress-strain curves representing the evaluation results of tensile properties of Examples 1 to 4 and Comparative Example 1, and FIG. 2 shows stress-strain curves representing the evaluation results of tensile properties of Examples 5 to 9 and Comparative Example 2. Young's modulus was calculated based on the highest slope value in the initial part of the curve, and the yield tensile strength was the tensile strength at the point where the difference between Young's modulus and the slope began to exceed 3% or more. [Table 3]

[0091] As shown in Table 3, Examples 1 to 4 are excellent in tensile properties including tensile strength at yield, Young's modulus, maximum tensile strength, and elongation at break, and are particularly excellent in tensile strength at yield and Young's modulus. In addition, Examples 3 and 4, which further contain a compatibilizer, are also excellent in maximum tensile strength and elongation at break compared to the case where no compatibilizer is used.

[0092] On the other hand, it was confirmed that Comparative Example 1, in which only polybutylene adipate terephthalate was used, was inferior in yield tensile strength and Young's modulus. [Table 4]

[0093] From Table 4, it was confirmed that Examples 5 to 9 were excellent in tensile properties including yield tensile strength, Young's modulus, maximum tensile strength, and elongation at break, and in particular, yield tensile strength and Young's modulus were remarkably excellent.

[0094] On the other hand, it was confirmed that Comparative Example 2, in which only polybutylene adipate terephthalate was used, had poor yield tensile strength and Young's modulus, and Comparative Example 3, in which polylactic acid was used, had poor Young's modulus.

Claims

1. including hydroxyalkanoate-lactide copolymer and polybutylene adipate terephthalate (PBAT); Biodegradable film.

2. Further comprising thermoplastic starch. The biodegradable film according to claim 1 .

3. The thermoplastic starch includes at least one selected from the group consisting of rice starch, wheat starch, corn starch, sweet potato starch, potato starch, tapioca starch, cassava starch, and modified starches thereof; The biodegradable film according to claim 2 .

4. The hydroxyalkanoate-lactide copolymer is a 3-hydroxypropionate-lactide copolymer. The biodegradable film according to claim 1 .

5. The 3-hydroxypropionate-lactide copolymer is a block copolymer in which polylactic acid prepolymer and poly(3-hydroxypropionate) prepolymer are polymerized. The biodegradable film according to claim 4.

6. At least one of the polylactic acid prepolymer and the poly(3-hydroxypropionate) prepolymer has a weight average molecular weight of more than 20,000 g / mol and not more than 50,000 g / mol; The biodegradable film according to claim 5 .

7. the weight ratio of the polylactic acid prepolymer to the poly(3-hydroxypropionate) prepolymer is from 95:5 to 50:50; The biodegradable film according to claim 5 .

8. The 3-hydroxypropionate-lactide copolymer has a total crystallinity of the polylactic acid block and the poly(3-hydroxypropionate) block calculated by the following Equations 1 and 2 of 20 to 100: The biodegradable film according to claim 5 . [Formula 1] Crystallinity of polylactic acid block (Xc_ PLA )=[(PLA Tm area)-(PLA Tcc area)] / 93.7 (In Equation 1, the PLA Tm area is an integral value of a peak at the melting temperature (Tm) of the polylactic acid (PLA) block in the block copolymer measured by time scanning calorimetry, and the PLA Tcc area is an integral value of a peak at the crystallization temperature (Tcc) of the polylactic acid block in the block copolymer measured by time scanning calorimetry.) [Formula 2] Crystallinity of poly(3-hydroxypropionate) block (Xc_ P(3HP) )=[(P(3HP) Tm area)-(P(3HP) Tcc area)] / 64 (In Equation 2, the P(3HP) Tm area is an integral value of a peak at the melting temperature (Tm) of the poly(3-hydroxypropionate) (P(3HP)) block in the block copolymer measured by differential scanning calorimetry, and the P(3HP) Tcc area is an integral value of a peak at the crystallization temperature (Tcc) of the poly(3-hydroxypropionate) block in the block copolymer measured by differential scanning calorimetry.)

9. The hydroxyalkanoate-lactide copolymer has a weight average molecular weight of 50,000 to 300,000. The biodegradable film according to claim 1 .

10. The weight ratio of the hydroxyalkanoate-lactide copolymer and polybutylene adipate terephthalate (PBAT) is 5:95 to 50:50; The biodegradable film according to claim 1 .

11. The thermoplastic starch is contained in an amount of 10 to 100 parts by weight per 100 parts by weight of the total of the hydroxyalkanoate-lactide copolymer and polybutylene adipate terephthalate (PBAT). The biodegradable film according to claim 2 .

12. The biodegradable film further comprises a compatibilizer. The biodegradable film according to claim 1 .

13. The compatibilizer includes a repeating unit represented by the following formula 1: The biodegradable film according to claim 12. [Chemical formula 1] 【Chemistry 1】 In the above Chemical Formula 1, R 1 ~R 6 each independently represents hydrogen, deuterium, hydroxy, nitro, amino, a substituted or unsubstituted alkyl having 2 to 60 carbon atoms, a substituted or unsubstituted alkoxy having 2 to 60 carbon atoms, a substituted or unsubstituted alkenyl having 2 to 60 carbon atoms, a substituted or unsubstituted cycloalkyl having 4 to 60 carbon atoms, a substituted or unsubstituted aryl having 6 to 60 carbon atoms, or a substituted or unsubstituted heteroaryl having 2 to 60 carbon atoms containing one or more of O, N, Si, and S; x, y, and z each independently represent an integer of 1 to 20.

14. The compatibilizer is contained in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the biodegradable film. The biodegradable film according to claim 12.

15. The biodegradable film has a yield tensile strength of 7 MPa or more as measured by ASTM D882-07; The biodegradable film according to claim 1 .

16. The biodegradable film has a Young's modulus of 80 MPa or more as measured by ASTM D882-07. The biodegradable film according to claim 1 .

Citation Information

Patent Citations

  • Bio plastic composition

    KR1020130074607A

  • Position measuring system using a personal mobility docked on a wireless charging station

    KR1020230029107A

  • Polymer composition

    US20160060451A1